Evaluation of CIPP in Distance Learning - Darul Prayogo, Amad Narto, Agus Wahyudi,Sabtuti Martikasari (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Distance learning is expected to be a solution in improving the quality of learning as well as the quality and independence of cadets, to build humane communication between cadets and lecturers as well as to fellow cadets.Learning by distance learning is teaching and learning activities using internet-based technology. Teaching and learning activities, not only uploading teaching materials to be accessed by cadets, but lecturers must also carry out an evaluation of their teaching and learning activities,The evaluation model used in this research is the CIPP model related to the implementation of distance learning. The analysis technique used is descriptive statistics.In the Context component, 44.68% stated that it was not good. The input component has an average score of 41 which is located at the score interval 33 - 42, which is included in the Good category. Process component, an average score of 82 which lies in the score interval 65 - 84 is included in the Good category. Product component, as many as 69 respondents which amounted to 48.94% said it was not good.